Permafrost creep and rockglaciers - Barsch, Dietrich (Permafrost and periglacial processes, 1992)
Active rockglaciers are discussed as the visible expression of creep of alpine or mountain permafrost. They are mainly formed below talus slopes (talus rockglaciers) and below lateral and terminal moraines (debris rockglaciers). Rockglaciers prefer continental, comparatively dry, winter-cold mountains. They are not well developed in high maritime and humid tropical mountains. Active rockglaciers are indicators of active mountain permafrost and, thus, of great geoecological information value.
Elektronische Reproduktion der Druck-Ausgabe 3. August 2006
Gesehen am 13.03.2023